Disability as scenic materiality: assistive technology and Its poetic possibilities (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article explores the use of assistive technology in theater, focusing on the creative possibilities that arise from integrating this technology into the theatrical scene, once it is understood as scenic materiality. It discusses the experiences of the shows “Happy New Year” and “Nicole Wolfman” and the work developed by the group “Signatores”, which use disability as a scenic materiality through the presence of assistive technologies on stage. The research suggests that disability can be a creative power, contributing to artistic practices for/with/by people with disabilities from the perspective of Cultural Accessibility.
Keywords: cultural accessibility; scenic materiality; assistive technology